Endocrine Disrupting Compounds Removal Methods from Wastewater in the United Kingdom: A Review - China K. Gadupudi; Louis Rice; Libin Xiao; Komali Kantamaneni (Sci, 2021)
Endocrine disrupting compounds (EDCs) are contaminants with estrogenic or androgenic activity that negatively impact human and animal communities. These compounds have become one of the most significant concerns for wastewater treatment in recent decades. Several studies have evaluated EDC removal methods from wastewater across the globe, including the United Kingdom (UK). Accordingly, the current study reviews EDC removal methods from municipal/domestic wastewater in the United Kingdom (UK) for the period of 2010–2017. The current study analysed original research articles (250), review articles (52), short communication (43), and other associated documents via the ScienceDirect.com database. A total of 25 published articles, which covered EDC removal methods from UK wastewaters, were reviewed rigorously. The research highlights that despite the relative efficacy of existing chemical and physical methods for removing certain EDCs from wastewater, there is emerging evidence supporting the need for more widespread application of nature-based and biological approaches, particularly the use of biofilms. The analysis reveals that there have been relatively few research studies on EDC removal methods carried out in the UK in the 2010–2017 period. Only four papers addressed the removal of specific endocrine disrupting compounds from UK municipal wastewater, and none of the studies addressed EDC removal by using direct biofilms. Finally, this review suggests that more research is needed to remove EDCs, particularly through the application of biofilms, from municipal wastewater in current scenarios.